Morphological and Physiobiochemical Changes in Dalbergia sissoo Roxb. Seed during its Development - Joshi, Geeta; Thapliyal, R. C.; Phartyal, S. S.; Nayal, J. S. (Indian Forester, 2008)
To determine the developmental stage at which the seed quality was maximum, Dalbergia sissoo pods were harvested at different periods from 15 to 255 days after anthesis (DAA). Pod and seed length, width, fresh weight, dry weight, moisture content, germination, colour and nitrogen, calcium, magnesium, potassium and phosphorus content were recorded. Maximum dry weight and minimum fresh weight was attained at 210 DAA the stage of mass maturity. Physiological maturity in seeds of Dalbergia sissoo was attained 240 days after anthesis (DAA), when the pod and seed turned light brown in colour and attained maximum germination percentage and minimum moisture content.